Different types of soil stabilization techniques - Đurđevac Vanja; Ignjatović Snežana; Ignjatović Dragan; Savić Dragana (Mining and Metallurgy Engineering Bor)
Soil stabilization is the process of improving physical, mechanical and dynamical properties of soil and increasing the bearing capacity. During the construction of a structure (road, building, etc.), it is necessary that the soil, where the structure will be located, meets the designed characteristics (physical, mechanical and deformation). In case, during the examination of the said soil, it is determined that it does not meet the given criteria, the improvement of the soil is started. This paper will describe the basic principles and types of soil stabilization.